The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.ppat.1004770
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Imatinib Induce Myelopoiesis and Enhance Host Anti-microbial Immunity

Abstract: Imatinib mesylate (Gleevec) inhibits Abl1, c-Kit, and related protein tyrosine kinases (PTKs) and serves as a therapeutic for chronic myelogenous leukemia and gastrointestinal stromal tumors. Imatinib also has efficacy against various pathogens, including pathogenic mycobacteria, where it decreases bacterial load in mice, albeit at doses below those used for treating cancer. We report that imatinib at such low doses unexpectedly induces differentiation of hematopoietic stem cells and progenitors in the bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 85 publications
1
62
0
1
Order By: Relevance
“…Several protein kinase inhibitors are available for clinical use. 129 Imatinib, a tyrosine kinase inhibitor, reduces bacterial load and lung pathology, likely by enhancing autophagy, phagosomal acidification and myeloid cell mobilization, [130][131] and is currently being tested for its safety and immunogenicity as repurposed TB treatment. Adenosine monophosphate-activated protein kinase (AMPK) regulates cellular energy levels, T-cell differentiation and development of memory.…”
Section: Kinase Modulatorsmentioning
confidence: 99%
“…Several protein kinase inhibitors are available for clinical use. 129 Imatinib, a tyrosine kinase inhibitor, reduces bacterial load and lung pathology, likely by enhancing autophagy, phagosomal acidification and myeloid cell mobilization, [130][131] and is currently being tested for its safety and immunogenicity as repurposed TB treatment. Adenosine monophosphate-activated protein kinase (AMPK) regulates cellular energy levels, T-cell differentiation and development of memory.…”
Section: Kinase Modulatorsmentioning
confidence: 99%
“…The tyrosine kinase inhibitor imatinib has emerged as a host-directed therapy for TB and other infections (23, 39, 40). In human macrophages imatinib was shown to induce the v-ATPase, leading to lysosome acidification and antimicrobial activity against M. tuberculosis (23).…”
Section: Resultsmentioning
confidence: 99%
“…7,11,13,14 these subtypes were impacted by flagellin treatment, we performed flow cytometry analysis on LSK cells from flagellin-or PBS-treated WT B6 mice using the recently defined signaling lymphocytic activation molecule (SLAM) code, which is capable of distinguishing LT-HSC, ST-HSC, and MPP subtypes. 14,25,26 This cellular identification protocol indicated that flagellin did not increase the level or alter the proliferative status of LT-HSCs (supplemental Figure 7A-C). Rather, flagellin treatment drove the proliferation of ST-HSCs and myeloid precursors MPP2 and especially MPP3, whose levels increased 10-fold following flagellin treatment ( Figure 5A-E).…”
Section: Flagellin Treatment Preferentially Induces Hematopoietic Promentioning
confidence: 97%
“…Markers for LT-HSCs, ST-HSCs, and MPP1-MPP4 are previously described. 14,25,26 In cell proliferation assays, intracellular staining of allophycocyanin-conjugated anti-BrdU and 7-aminoactinomycin D (7-AAD) were performed following surface staining. Stained cells were analyzed on a BD Fortessa flow cytometer.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%